2004
DOI: 10.1007/s00198-004-1733-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency in adolescent males in Southern Tasmania: prevalence, determinants, and relationship to bone turnover markers

Abstract: There are limited data on vitamin D insufficiency in healthy children. The aim of this study was to describe the prevalence and determinants of vitamin D insufficiency and its association with bone turnover in adolescent boys (N = 136, mean age 16 years). Sun exposure and physical activity were assessed by questionnaire. Vitamin D stores were assessed by serum 25-hydroxyvitamin D3 (25[OH]D3). Bone turnover was assessed by bone-specific alkaline phosphatase (BAP) and urinary pyridinoline (PYR) to creatinine (Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 29 publications
4
58
0
2
Order By: Relevance
“…Two Tasmanian studies of 8-year-old (19) and adolescent (20) children found that serum 25(OH)D was correlated with usual levels of sun exposure in the season preceding the measurements [r = 0.20, P < 0.01 (19) and r = 0.23, P = 0.01 (20) for exposure during school holidays; r = 0.16, P = 0.02 (19) and r = 0.23, P = 0.01 (20) for exposure during weekends]. Lifetime sun exposure in adults measured by a calendar method was associated with actinic damage in the study by English et al (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two Tasmanian studies of 8-year-old (19) and adolescent (20) children found that serum 25(OH)D was correlated with usual levels of sun exposure in the season preceding the measurements [r = 0.20, P < 0.01 (19) and r = 0.23, P = 0.01 (20) for exposure during school holidays; r = 0.16, P = 0.02 (19) and r = 0.23, P = 0.01 (20) for exposure during weekends]. Lifetime sun exposure in adults measured by a calendar method was associated with actinic damage in the study by English et al (8).…”
Section: Discussionmentioning
confidence: 99%
“…Three validity studies have been conducted in school children (18)(19)(20), showing that these children are able to recall recent and current habitual sun exposure. In adolescents, polysulfone badge recordings of UVR exposure on 4 weekend days in late spring correlated well with two questions on habitual sun exposure (correlation 0.35 for time in the sun, 0.29 for activities outside; ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13) Serum 25(OH)D levels are considered the best marker of vitamin D status and have been used commonly to assess the prevalence of vitamin D deficiency/insufficiency in healthy children and adolescents. (9,10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) However, a clear understanding of the biologic significance of given concentrations of circulating 25(OH)D is still lacking, and reference ranges for vitamin D are being reassessed on the basis of what constitutes a normal concentration compared with optimal concentrations. (27)(28)(29) Most clinicians agree that serum 25(OH)D levels below 25 to 30 nmol/L (10 to 12 ng/mL) may lead to nutritional rickets, hypocalcemic convulsions, dental problems, and poor growth in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that in healthy Caucasian adolescent boys aged 16-18 years, there was a significant association between sports-related sun exposure and vitamin D status. 41 Additionally, a study of Chinese girls aged 15 years also observed that lifestyle factors, such as participation in organized sports and time spent exercising, both at school and in leisure time, showed significant and independent positive association with 25(OH)D concentration. 42 This can be explained by the fact that most exercise by these subjects was taken outdoors, so that their higher vitamin D status may have resulted from an increased exposure to sunlight.…”
Section: Discussionmentioning
confidence: 97%